Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1023/a:1021043529923
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Aliphatic and Aromatic Probes on Bovine Serum Albumin: Influence on Its Structural and Physicochemical Characteristics

Abstract: Bovine serum albumin was chosen as a model protein to study the effect of the functionalization of the epsilon-NH2 of lysine residues with different carbon chains on the physical properties of proteins. Thus, BSA has been acylated and sulfonylated by means of anhydrides and sulfonyl chlorides, respectively. The secondary structures of modified BSA, studied by far-UV CD, showed very slight changes except after sulfamidation. However, near-UV CD and intrinsic fluorescence spectra revealed important conformationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…To minimize this problem, an excess of acid derivative is generally used (18). Thus, different ratios of rapeseed hydrolysate and acyl chloride were tested to find the best balance between the amount of reagent used and the degree of modification reached (Table 1).…”
Section: Characterization and Acylation Of The Rapeseed Hydrolysatementioning
confidence: 99%
See 1 more Smart Citation
“…To minimize this problem, an excess of acid derivative is generally used (18). Thus, different ratios of rapeseed hydrolysate and acyl chloride were tested to find the best balance between the amount of reagent used and the degree of modification reached (Table 1).…”
Section: Characterization and Acylation Of The Rapeseed Hydrolysatementioning
confidence: 99%
“…It can be observed that the degree of modification increased from C 6 to C 10 acyl chlorides and then decreased. These different percentages of acylation are related to their different reactivity and stability in aqueous media (18). Final freeze-dried acylated hydrolysates had a peptide content that ranged from 42 to 48%.…”
Section: Characterization and Acylation Of The Rapeseed Hydrolysatementioning
confidence: 99%
“…The k q for the TYP-ATR system at different temperatures is presented in Table 1 . The values of k q were found higher than the value of the collision quenching constant (2 × 10 10 M −1 s −1 ), suggestive of a static quenching mechanism in the TYP-ATR system [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The carboxylic acids are beforehand activated in the form of anhydride and the most frequently used are acetic anhydride and even more succinic anhydride. Generally, acylation is performed at room temperature by adding the anhydride (1–3 equivalents per lysine group) dropwise to the protein solution, at pH ≅ 9 to keep amines in non‐protonated form (Gerbanowski et al., 1999).…”
Section: Chemical Reactions On the Amine Functions Of Caseinmentioning
confidence: 99%
“…The carboxylic acids are beforehand activated in the form of anhydride and the most frequently used are acetic anhydride and even more succinic anhydride. Generally, acylation is performed at room temperature by adding the anhydride (1-3 equivalents per lysine group) dropwise to the protein solution, at pH ≅ 9 to keep amines in non-protonated form (Gerbanowski et al, 1999). Succinylation of food proteins is listed in a recent review where the properties of water solubility, emulsification, foaming, thermal stability, rheology, nutrition, encapsulation, and drug release are highlighted (Basak & Singhal, 2022).…”
Section: N-acylation Of Caseinmentioning
confidence: 99%